“A Good Doctor”: Building a Physician’s Authority in the Selected Treatises of the Hippocratic Corpus - Wieżel, Iwona (2019)
There exists communis opinio (Jouanna, 1984) on a group of treatises that should be considered “oral” in the sense of containing signs of composition for speech-making within the “Hippocratic Collection.” In this article, we try to demonstrate the specific congruence of the goals between the rhetoric and medical texts, in which the one who speaks is the one who deserves the label of “a good doctor.” This message, though composed in an epideictic way, may also be considered as relying on rhetorical strategies, which imply a building up of the specific position of the speaker, whether it be an orator, a historian, or a medical writer in classical Greece. Winning this position in the latter case assumes, in our opinion, communicational success between the doctor and a patient, and professional gain. We have tried to delineate how those oral strategies work in an Ancient oratorical context in medical topics where the speaker persuades his audience, establishing both a doctor and the doctor-patient relationship.
Keywords: orality; ancient medicine; authority